Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1096/fasebj.11.5.9141500
|View full text |Cite
|
Sign up to set email alerts
|

Connectin/titin, giant elastic protein of muscle

Abstract: The structure and function of the giant elastic protein connectin/titin are described on the basis of recent investigations. The 3000 kDa protein links the Z line to the myosin filament in striated muscle sarcomeres. The NH2-terminal region of connectin filament is involved in the Z line binding, and the COOH-terminal region is bound onto the myosin filament with an overlap between the counter-connectin filaments at the M line. The PEVK region in the I band is shown to be mainly responsible for passive tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(124 citation statements)
references
References 34 publications
2
116
0
6
Order By: Relevance
“…For example, in tendon cells subjected to cyclic stretching of 5% strain at 1 Hz for 6 h in vitro, expression of collagen type I was increased at the transcriptional level, as was the expression of several other genes including connectin, cystatin, and calmodulin (Banes et al, 1999). Connectin is an elastic protein whose role may be as a shock cord to keep sarcomeres from pulling apart (Maruyama, 1997). Its presence in tendon could serve to prevent cell syncytia from pulling apart under dynamic loads.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
“…For example, in tendon cells subjected to cyclic stretching of 5% strain at 1 Hz for 6 h in vitro, expression of collagen type I was increased at the transcriptional level, as was the expression of several other genes including connectin, cystatin, and calmodulin (Banes et al, 1999). Connectin is an elastic protein whose role may be as a shock cord to keep sarcomeres from pulling apart (Maruyama, 1997). Its presence in tendon could serve to prevent cell syncytia from pulling apart under dynamic loads.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
“…Kettin is one of the first proteins to colocalize with actin during the early stages of myofibrillogenesis (Ayme-Southgate et al, 2004), and genetic analysis has shown that it is essential for myofibril assembly in the fruit fly (Hakeda et al, 2000). The sequence of kettin contains 35 immunoglobulin-like (Ig) repeats separated by short linker sequences (Hakeda et al, 2000;Kolmerer et al, 2000) and is related to the connectin/titin family of giant elastic proteins (Maruyama, 1997;Gautel et al, 1999;Gregorio et al, 1999;Maruyama and Kimura, 2000;Granzier et al, 2002). However, kettin does not have fibronectin-like, elastic PEVK, or kinase domains, and seems to be a uniquely evolved member of the connectin/titin family of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…T itins are 3.0-3.7 MDa filamentous proteins extending between the Z-and M-lines of the sarcomere (1)(2)(3)(4). Titin is a tandem array of Ig type C2 and fibronectin (FN) type III domains (Ϸ300 per molecule) interspersed with unique sequences, most notably the Pro-, Glu-, Val-, and Lys-rich PEVK segment, and the N2A and N2B segments (5).…”
mentioning
confidence: 99%